Study protocol for developing deprescribing clinical practice guidelines: evidence-based GRADE methodology and a Delphi consensus method - Hui Wen Quek; Amy Page; Kenneth Lee; Christopher Etherton-Beer (BMC Geriatrics)
Abstract Background Deprescribing has emerged as a strategy to reduce the use of potentially inappropriate medicines, particularly in older people. Evidence-based deprescribing clinical practice guidelines are a key enabler in integrating deprescribing into routine care. This protocol outlines the development of deprescribing clinical practice guidelines targeting many commonly prescribed medicines for older people, specifically focusing on applying the evidence-based Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology alongside a Delphi consensus-building process. Methods The guideline development process follows the World Health Organisation Handbook for Guideline Development, Australian National Health and Medical Research Council Guideline Development Methodology, and the Appraisal of Guidelines for Research & Evaluation (AGREE) II Instrument with adaptations made to suit the guideline’s purpose, available resources, and the urgent need for recommendations to support clinical decision-making. This project is developed by a multidisciplinary healthcare team, representatives from professional organisations, and patient or carer stakeholders. The development involves a two-part sequential approach: evidence-deriving using a structured GRADE methodology and consensus-building processes using a standardised Delphi approach. Firstly, a comprehensive systematic review and meta-analysis of the literature was conducted to identify evidence related to deprescribing in older people, with the evidence presented and certainty assessed using the GRADE framework. Where quality evidence is available, evidence-based recommendations will be formulated following the evidence-to-decision GRADE framework. For areas with insufficient quality evidence, consensus-based recommendations will be developed using a modified Delphi method. Additional good practice statements will be developed where necessary to facilitate the practical application of these recommendations. Discussion Given the large scope of the currently proposed guidelines, the proposed approach discussed in this protocol is adapted based on several important considerations on the practical, operational, and resource issues. Given deprescribing is an emerging area and the limited availability of evidence for some drug classes, expert consensus and input from patient representatives offer a valuable alternative for recommendation development. The final guideline will provide clinicians with broad guidance for deprescribing common medicines used in older people that complement existing single-drug-class deprescribing guidelines and other treatment guidelines. Trial Registration Not applicable.